HISTORY OF STUDY OF VERBAL PREVERBS IN FINNO-UGRIC LINGUISTICS - Nakhracheva, Galina Leonidovna (V mire nauchnykh otkrytiy, 2014)
The study of lexical fund of the Khanty language and peculiarities of its formation remain one of the most important tasks of the modern Khanty language. The article integrates the works of national researchers on the subject, analyzes the semantics of verbal preverbs that form the destructive verbs in the Khanty language (based on Shuryshkarsky dialect). The aim of the study is semantics and lexical compatibility of the Khanty destructive action verbs with preverbs. As part of this goal the following issues are solved: 1. To examine and summarize the works of national researchers on the subject. 2. To identify the layer of the verbs formed by the preverbs. 3. To describe the semantics of the verbs. Research material is mainly based on the samples of colloquial language and examples from the works of Khanty writers, as well as the materials from the national press "Luh Avat." Moreover, the actual material, collected by us from monolingual and bilingual dictionaries, educational and scientific publications, was used in the work. My own linguistic competence and work with consultants helped me in the research too. Изучение лексического фонда хантыйского языка и особенностей его формирования остаются одной из важных задач современного хантыйского языка. В данной статье обобщаются труды отечественных исследователей по данной теме, исследуется семантика глагольных превербов, которые формируют деструктивные глаголы в хантыйском языке (на материале шурышкарского диалекта). Целью исследования является семантика и лексическая сочетаемость хантыйских глаголов деструктивного действия с превербами. В рамках поставленной цели решаются следующие задачи: 1. Изучить и обобщить труды отечественных исследователей по данной теме. 2. Выявить пласт глаголов формируемых данными превербами. 3. Описать семантику этих глаголов. Материалом исследования послужили в основном образцы разговорной речи и примеры из произведений хантыйских писателей, а также из материалов национальной печати «Лух Ават». Кроме того, использовался фактический материал, собранный нами из одноязычных и двуязычных словарей, учебных и научных изданий; помогала так же собственная языковая компетенция и работа с информантами.